A comparative immunohistochemical study of the "biphasic ductules" in adenoid cystic carcinoma, pleomorphic adenoma and epi-myoepithelial carcinoma - Patel, Kunel (My University, 2014)
Immunohistochemistry has been used as an aid in the histological diagnosis of salivary gland neoplasms as they often show overlapping histomorphological growth patterns.
Keywords: Neoplasms by Histologic Type